INVERSE MONTE CARLO METHOD FOR A NONINVASIVE COMPUTERISED PIGMENTATION ANALYSIS - ,, HERMAWAN NUGROHO (2014)
An impairment of skin can lead to an illness with a considerable disability that requires treatment and affects psychologically. A common type of skin disease is pigmentation disorder. a condition that causes the skin to appear lighter or darker. This condition is due to abnormal melanin production. From the literature, currently there is no in vivo method that is non-invasive to measure accurately melanin types (eumelanin and pheomelanin) and quantities used to assess the severity of skin pigmentation disorder and treatment efficacies.